The efficacy and economic evaluation of roxadustat treatment for anemia in patients with kidney disease not receiving dialysis. (3rd July 2020) - Hu, Zhanhong; Tao, Hong; Shi, Aiming; Pan, Jie
ABSTRACT: Background: This study aimed to assess the efficacy, tolerance, and cost-effectiveness of roxadustat treatment for anemia in patients with chronic kidney disease not receiving dialysis (CKD ND). Methods: A meta-analysis was conducted to evaluate the clinical efficacy and tolerance of roxadustat for the correction of anemia associated with CKD ND, and a Markov model was developed to evaluate the cost-effectiveness of roxadustat compared with a placebo. Results: The meta-analysis results showed that compared with a placebo, roxadustat treatment was associated with a remarkably higher rate of clinical response and the differences in the rate of adverse events between these two regimens were not significant. Moreover, roxadustat treatment (70 mg, three times per week) provided an additional 0.49 QALYs at a cost of 12, 526 in the time horizon of 5 years, resulting in an ICER of 25, 563 per QALY, with approximately 60% probability to be cost-effective at a 29, 295 per QALY willingness-to-pay (WTP) threshold from the perspective of Chinese medical system. Conclusion: For the treatment of anemia in Chinese patients with CKD ND, roxadustat is much more effective than a placebo; moreover, it is cost-effective at conventional WTP thresholds.